ULSOSEAL Technique: A Unique Technique to Achieve Hemostasis Using ExoSeal in High-Risk Patients after Common Femoral Artery Puncture - Yohsuke Honda; Shinsuke Mori; Tomoya Fukagawa; Toshihiko Kishida; Takahide Nakano; Shigemitsu Shirai; Masafumi Mizusawa; Kenji Makino; Masakazu Tsutsumi; Norihiro Kobayashi; Masahiro Yamawaki; Yoshiaki Ito (Journal of Interventional Cardiology)
This study aimed to assess the safety and feasibility of the ULtrasound-guided uSe Of exoSEAL technique (ULSOSEAL technique) in patients at a high risk of complications following the use of ExoSeal. ExoSeal is a novel, completely extravascular hemostatic device that can treat punctures of the common femoral artery; however, it is not preferable for use in cases that require hemostasis of complex puncture sites. From November 2019 to August 2020, the ULSOSEAL technique was performed in 35 patients with implanted stents (6 patients, 17%), severe calcification (32 patients, 91%), and plaque (7 patients, 20%) around the puncture site; the presence of these conditions is usually undesirable when using ExoSeal. The antegrade approach was used in 22 patients (71%). The size of the ExoSeal used was 5 Fr (13 patients, 37%), 6 Fr (21 patients, 60%), and 7 Fr (1 patient, 2%). Technical success was achieved in 34 patients (97%), while ExoSeal malfunction occurred in 1 patient. There was no incidence of vessel occlusion, pseudoaneurysm, arteriovenous fistula, infection, and secondary bleeding. One patient developed a hematoma (>5 cm in size); however, it occurred before the use of ExoSeal due to side leakage from the inserted sheath. The ULSOSEAL technique was safe and feasible for hemostasis in patients who were considered unsuitable for the ExoSeal device.